HER2 Amplification Status in Feline Mammary Carcinoma: A Tissue Microarray–Fluorescence In Situ Hydridization–Based Study. Issue 2 (March 2019) - Muscatello, Luisa Vera; Di Oto, Enrico; Sarli, Giuseppe; Monti, Valentina; Foschini, Maria Pia; Benazzi, Cinzia; Brunetti, Barbara
Human epidermal growth factor receptor 2 (HER2) is a tyrosine kinase receptor overexpressed in a subset of breast cancer due to HER2 gene amplification. HER2 protein is expressed in feline mammary carcinomas, but little is known about its cytogenetic alterations. The aim of this study was to evaluate HER2 gene amplification status and its correlation with HER2 protein expression in feline mammary carcinomas. Feline mammary carcinomas were retrospectively selected and immunohistochemically (IHC) evaluated for HER2 protein expression. All the HER2 IHC-positive (3+) and equivocal (2+) cases and a subset of negative cases (0/1+) were selected for fluorescence in situ hybridization (FISH). Dual-core tissue microarrays were prepared for FISH. IHC and FISH were evaluated according to the 2013 American Society of Clinical Oncology/College of American Pathologists guidelines. The study included 107 feline mammary carcinomas from 88 queens. HER2 protein expression was positive (3+) in 7 cases (6.5%), equivocal (2+) in 48 cases (45%), and negative (0/1+) in 52 cases (48.5%). HER2 status was indeterminate in 8 feline mammary carcinomas (12%), amplified in 3 (4%), equivocal in 4 (6%), and nonamplified in 53 (78%). HER2 gene amplification and protein expression were significantly positively correlated ( R = 0.283; P < .0001). HER2 gene is amplified in a subset of feline mammary carcinomas despite the HER2 positive or equivocal protein expression, but it remains to be determined if the HER2 amplification is a gene alteration that drives mammary tumor carcinogenesis or only a bystander passenger mutation.